Pełnomocnictwo w administracyjnym postępowaniu egzekucyjnym - Drelichowska, Angelika (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
This article presents the problems of the power of attorney in Polish administrative enforcement proceedings. The main goal of this paper is to analyse — for the first time in Polish legal doctrine — the specificity of the power of attorney in administrative enforcement proceedings, especially against the attorney in administrative proceedings provided by the Code of Administrative Procedure. Analyzing and contrasting domestic regulations of both administrative proceedings and administrative enforcement proceedings, the author hereof reaches the conclusion that the power of attorney granted in administrative proceedings does not entail legal consequences in administrative enforcement proceedings, although the current act on administrative enforcement proceedings does not contain any direct regulations on this institution but only the referencing provision to the Code of Administrative Procedure. The author also discusses the structural elements of the power of attorney in administrative enforcement proceedings with a special focus on the legal capacity to grant somebody the power of attorney as well as to act as an attorney, subjective scope and formal requirements of this institution of law.
Keywords: pełnomocnictwo; egzekucja administracyjna; wymogi formalne pełnomocnictwa w egzekucji administracyjnej; zakres podmiotowy pełnomocnictwa w egzekucji administracyjnej; zdolność do udzielania pełnomocnictwa i do wykonywania czynności pełnomocnika w egzekucji administracyjnej; obrady